2008
DOI: 10.2298/jsc0803341b
|View full text |Cite
|
Sign up to set email alerts
|

Cd(II) extraction in PEG(1550)-(NH4)2SO4 aqueous two-phase systems using halide extractants

Abstract: The extraction of Cd(II) was studied in an aqueous PEG-(NH 4 ) 2 SO 4 two-phase system, formed from a water-soluble polymer (poly(ethylene glycol), PEG) and an inorganic salt ((NH 4 ) 2 SO 4 ), in the presence of halide ions. In the absence of a suitable extracting agent, Cd(II) remains predominantly in the salt-rich phase of the extraction system. By addition of halide ions as extractants, Cd(II) is extracted into the PEG-rich phase due to the formation of cadmium halide species. The efficiency of the extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In recent years an increasing amount of research has focused on metal extraction by means of aqueous biphasic systems. Ammar et al (2013) investigated the extraction behaviour of Cd(II), Cu(II), Fe(II) and Zn(II) in an aqueous biphasic system composed of PEG and sodium sulphate in the presence of KI and KSCN as extractants; Cd(II) extraction was investigated by Bulgariu and Bulgariu (2008) in a PEG 1550-(NH 4 ) 2 SO 4 system. Dzherayan et al (2006) studied the extraction of gallium from alkaline carbonate solutions with phenylfluorone in the PEG-sodium carbonate-water system; copper extraction with a PEG 3,350-ammonium sulphate-water system was studied by Fontana and Ricci (2000) in the presence of 1,10 phenanthroline as complexing agent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years an increasing amount of research has focused on metal extraction by means of aqueous biphasic systems. Ammar et al (2013) investigated the extraction behaviour of Cd(II), Cu(II), Fe(II) and Zn(II) in an aqueous biphasic system composed of PEG and sodium sulphate in the presence of KI and KSCN as extractants; Cd(II) extraction was investigated by Bulgariu and Bulgariu (2008) in a PEG 1550-(NH 4 ) 2 SO 4 system. Dzherayan et al (2006) studied the extraction of gallium from alkaline carbonate solutions with phenylfluorone in the PEG-sodium carbonate-water system; copper extraction with a PEG 3,350-ammonium sulphate-water system was studied by Fontana and Ricci (2000) in the presence of 1,10 phenanthroline as complexing agent.…”
Section: Introductionmentioning
confidence: 99%
“…The system consists of PEG-(NH 4 ) 2 SO 4 -water, since it has been often employed in the literature for the extraction of several metal ions (Fontana and Ricci, 2000;Bulgariu and Bulgariu, 2008). Indium partitioning in the selected ABS was investigated in the presence of 1,10 phenanthroline, which is a traditional ligand employed in coordination chemistry (Bencini and Lippolis, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23]. It has also been shown that gold(I), when it is complexed with cyanide can be quantitatively extracted (>96%) in aqueous PEGbased two-phase system, where Na 2 SO 4 is used as phase-forming inorganic salt [24].…”
Section: Introductionmentioning
confidence: 99%
“…However, most work on aqueous two-phase extraction emphasized the effect of various experimental operation parameters on the distribution ratios of objectives, but ignored the influence of phase-forming behaviors and morphology variation of polymers [20][21][22]. Johansson's model derived from the Flory-Huggins theory [23] and the interaction model of phase-forming anions with PEO have been employed to qualitatively explain the driving force for the partition of target molecules and possible phase-forming mechanism of ATPS [3,24].…”
Section: Introductionmentioning
confidence: 99%